The iPhone developer's cookbook : building applications with the iPhone 3.0 SDK - Sadun, Erica (Developer's library, 2010)
"This book would be a bargain at ten times its price! If you are writing iPhone software, it will save you weeks of development time. Erica has included dozens of crisp and clear examples illustrating essential iPhone development techniques and many others that show special effects going way beyond Apple's official documentation." - Tim Burks, iPhone Software Developer, TootSweet Software "Erica Sadun's technical expertise lives up to the Addison-Wesley name. The iPhone Developer's Cookbook is a comprehensive walkthrough of iPhone development that will help anyone out, from beginners to more experienced developers. Code samples and screenshots help punctuate the numerous tips and tricks in this book." - Jacqui Cheng, Associate Editor, Ars Technica "We make our living writing this stuff and yet I am humbled by Erica's command of her subject matter and the way she presents the material: pleasantly informal, then very appropriately detailed technically. This is a going to be the Petzold book for iPhone developers." - Daniel Pasco, Lead Developer and CEO, Black Pixel Luminance "The iPhone Developer's Cookbook should be the first resource for the beginning iPhone programmer, and is the best supplemental material to Apple's own documentation." - Alex C. Schaefer, Lead Programmer, ApolloIM, iPhone Application Development Specialist, MeLLmo, Inc. "Erica's book is a truly great resource for Cocoa Touch developers. This book goes far beyond the documentation on Apple's Web site, and she includes methods that give the developer a deeper understanding of the iPhone OS, by letting them glimpse at what's going on behind the scenes on this incredible mobile platform." - John Zorko, Sr. Software Engineer, Mobile Devices "I've found this book to be an invaluable resource for those times when I need to quickly grasp a new concept and walk away with a working block of code. Erica has an impressive knowledge of the iPhone platform, is a master at describing technical information, and provides a compendium of excellent code examples." - John Muchow, 3 Sixty Software, LLC; founder, iPhoneDeveloperTips.com "This book is the most complete guide if you want coding for the iPhone, covering from the basics to the newest and coolest technologies. I built several applications in the past, but I still learned a huge amount from this book. It is a must-have for every iPhone developer." - Roberto Gamboni, Software Engineer, AT&T Interactive.